Challenges encountered by midwives performing basic neonatal resuscitation in health facilities in Kinshasa, Democratic Republic of the Congo - Eric M. Mafuta; Daniel K. Ishoso; Carl L. Bose; Benjamin H. Chi; Patricia Gomez; Ingunn A. Haug; Helge Myklebust; Antoinette K. Tshefu; Jackie K. Patterson (PLoS ONE, 2025)
Worldwide, an estimated five million children under the age of five die each year; 47% of these deaths occur during the neonatal period, and the vast majority in low- and middle-income countries. Events during labor are the cause of one quarter of neonatal deaths globally. Basic resuscitation with positive pressure ventilation reduces these deaths but is challenging to execute. To characterize barriers to implementation of basic neonatal resuscitation, we conducted a qualitative study using focus group discussions with midwives at three health facilities in Kinshasa, Democratic Republic of the Congo. We analyzed qualitative data using an inductive content approach in order to identify emergent themes and trends. Twenty-four midwives participated with a median age of 49 and over 80% with more than 10 years of clinical experience. We categorized challenges to implementing basic neonatal resuscitation into three themes with subthemes: 1) limited resources (subthemes: human resource limitations, inadequate and unprepared equipment, insufficient monitoring during labor); 2) inadequate simulated and clinical experience (subthemes: poor systems to support maintenance of skills, infrequent opportunity to resuscitate); 3) emotional burden of resuscitation (subthemes: decision-making under time pressure, tendency to stick to the routine, acute stress during resuscitation, moral distress after unsuccessful outcome). Our findings suggest that while simulation training is key, learning from clinical events may be a critical companion to address these barriers. We call for a new focus on developing and evaluating strategies that support providers in learning from every newborn resuscitation.